ChemInform Abstract: Synthesis of Biologically Active Seven‐Membered‐Ring Heterocycles. Issue 19 (13th May 2014) - Reekie, Tristan A.; Kavanagh, Madeline E.; Longworth, Mitchell; Kassiou, Michael
Abstract A brief account on established procedures for preparation of the title compounds is presented.